Factors predicting 30-day mortality after ERCP in patients with inoperable malignant hilar biliary obstruction: a single tertiary referral centre experience and systematic review. Issue 1 (17th March 2022) - On, Wei; Saleem, Muhammad A; Hegade, Vinod S; Huggett, Matthew T; Paranandi, Bharat; Everett, Simon M
Abstract : Objective: There is a paucity of studies in the literature body evaluating short term outcomes following endoscopic retrograde cholangiopancreatography (ERCP) in patients with inoperable malignant hilar biliary obstruction (MHBO). We aimed to primarily evaluate 30-day mortality in these patients and secondarily, conduct a systematic review of studies reporting 30-day mortality. Design: We conducted a retrospective analysis of all patients with inoperable MHBO who underwent ERCP at Leeds Teaching Hospitals NHS Trust between February 2015 and September 2020. Logistic regression models constructed from baseline patient data, the modified Glasgow Prognostic Score (mGPS) and Charlson Comorbidity Index (CCI) were evaluated as predictors of 30-day mortality. Results: Eighty-seven patients (49 males) with a mean age of 70.4 years (SD ±12.3) were included. Cholangiocarcinoma was the most common aetiology of MHBO affecting 35/87 (40.2%). Technical success was achieved in 72/87 (82.8%). The 30-day mortality rate was 25.3% (22/87), of which 16 were due to progression of underlying malignant disease. On multivariate analysis, only leucocytosis (OR 4.12, 95% CI 2.70 to 7.41, p=0.02) was an independent predictor of 30-day mortality. Neither mGPS (p=0.47) nor CCI with a cut-off value of ≥7 (p=0.06) were significant predictors of 30-day mortality. Conclusion: We demonstrated that 30-day mortality following ERCP for inoperable MHBO remains high despite technical success. Further studies are warranted to identify patients most appropriate for intervention.